Institutional options for sustainable irrigation : an evidence from Bulgaria - Ivan Penov (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2004)
This paper investigates a local problem of common pool resources (CPR), the solution of which needs a balance between the collective and private interests. In the political context we have a large group of actors with a short planning horizon and a lack of trust among them. CPR provision is organised in a centralised way. The state enforcement mechanism is weak and cannot protect the individuals or eventually back the collective decisions. The above problem is investigated in the case of irrigation in Bulgaria where water usage declined by nearly 85% during the period of transition. In addition, large parts of the existing canal systems were abandoned. Three groups of institutional options are investigated in the paper: improvement of the local level co-ordination; limiting the market imperfections, and strengthening the external conflict resolution and sanctioning mechanisms. The investigation of the above case led the author to conclusions that can be generalised for the case of CPR management during the period of transition. The transition process is not just a process of transferring western institutions to Eastern Europe, but also a process of spontaneous emerging of new institutions at local level. Therefore, we call for state intervention, not in the area of CPR provision, but in supporting local co-ordination.
Keywords: 330; Bewässerung; Allmenderessource; Agrarverfassung; Bulgarien